Sistem Informasi â€œAspirasiâ€: Sebuah Bentuk Penanganan Complain Perpustakaan Universitas Gadjah Mada - Nur Cahyati Wahyuni (IJAL (Indonesian Journal of Academic Librarianship), 2018)
Continuous improvement is the key word for a Library that has already implemented international standard organization (ISO) in its services. The library should pay attention to customer complaint as an input for improvement. UGM Library in coordination with Public Relations of Universitas Gadjah Mada, using Information System "ASPIRASI" (SIAP) as a communication channel to public. The ASPIRASI is managed by UGM Public Relation whom has authority to arrange complaint disposition. Observation and document study of Library ISO-Like and Aspirations of UGM indicate the existence of several factors that become the subject of complaints namely physical facilities, information access, rules of library, collection, information system, and libraryâ€™s human resource. In the future, with SIAP, continuous improvement could be made and the number of complaints decreases from year to year, or at least, there is no complaint about the same thing.